How to approach this? sequence {X_n } is defined by x_1 = sqrt ( 2) and X_n + 1 = sqrt ( 2 + X_n ) . Show that X_n + 1 > X_n for all integers n> 1

At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.

Get our expert's

answer on brainly

SEE EXPERT ANSWER

Get your free account and access expert answers to this and thousands of other questions.

A community for students.

How to approach this? sequence {X_n } is defined by x_1 = sqrt ( 2) and X_n + 1 = sqrt ( 2 + X_n ) . Show that X_n + 1 > X_n for all integers n> 1

Mathematics
See more answers at brainly.com
At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.

Get this expert

answer on brainly

SEE EXPERT ANSWER

Get your free account and access expert answers to this and thousands of other questions

\[X _{n} \] is defined by \[X _{1}=\sqrt{2}\] and \[X _{n+1}=\sqrt{2+X _{n}}\] show that \[X _{n+1} > X_{n}\] for all n>1
so have you tried a proof by induction?
How should I do that with this one?

Not the answer you are looking for?

Search for more explanations.

Ask your own question

Other answers:

First step is to show x(1)
Give some more hints please? Cause im just thinking recursive right now, and I dont know what xn is?
this is how your sequence x(n) is defined: \[x_n=\sqrt{2+x_{n-1}}\] well where x(1)=sqrt(2)
\[x_{n}>0 \text{ for integer } n>0 \\ \\ \text{ so showing } \\ x_nx_{n+1}^2\]
hint write out what x^2(n+2) is
are you still there?
yes, im just trying to understand writing it down
just in case you don't understand my non-latex I'm asking you to write \[x^2_{n+2} \text{ is } \\ \text{ and you really only know how to do in terms of the previous entry } \\ \text{ but still this is what I'm looking for }\]
\[x^2_{n+2}=2+x_{n+1}\] you do understand this is what I'm looking for?
and that we made the assumption that x(n+1)>xn earlier
\[x^2_{n+2}=2+x_{n+1}>2+x_n\] but guess what 2+x(n) is equal to?
\[x^2_{n+2}=2+x_{n+2}\]
?
yes plus one...
sorry
\[\sqrt{2}\]?
Yea I cant see the pattern...
\[\text{ we assumed } x_n2+x_n=x_{n+1}^2\]
the end
what do you mean with the end? do you have to the the induction steps with that?
have to do*
I didn't give the whole proof. You still have to show x(2)>x(1). But yeah we did the whole assumption thing that x(n)x(n+1) using our inductive assumption (hypothesis)
but the part you have to do isn't too hard it is just pluggin in n=1 into \[x_{n+1}=\sqrt{2+x_n}\]
then concluding x(2)>x(1) from that
I already did the other part of the proof
if you don't understand something I did let me know
Yea I will try some on paper now, I will tag you here with questions :) thanks for now!
Im putting in n=1 and gets that \[x _{2}=\sqrt{2+x _{1}}\] so \[x _{2}=\sqrt{2+\sqrt{2}}\] so \[x _{2}>x_{1}\] so we have prooven that the assumption is true for n=1 but the next step is to proove that its true for n=p and also true for p+1?
right which we have done above
we assumed \[x_nx^2_{n+1}\] remember we did this: \[x_{n+2}^2=2+x_{n+1}>2+x_n=x_{n+1}^2\]
which you know from that we have x(n+2)>x(n+1) since x^2(n+2)>x^2(n+1)
As long as we prove that \(X_n>0\) we are done. Since \(a>b\implies\sqrt{a}>\sqrt{b}\), \(X_n>0\implies X_{n+1}=\sqrt{2+X_n}=\sqrt{2+\sqrt{2+X_{n-1}}}>\sqrt{2+X_{n-1}}={X_n}\)
Yes but dont have to do it with all the right steps? 1) Inductionbase: you check if the assertion checks out for the lowest integer n. 2)Inductionassumption You assume that the assertion works with a integer n=p (Leftside_p=Rightside_p) 3)Inductionsteps: You show that if the assertion works with n=p it will work for n=p+1 also. I cant do that with this one...
Prove of \(X_{n+1}>X_n\): \[ X_1=\sqrt{2}\\ X_2=\sqrt{2+X_1}=\sqrt{2+\sqrt{2}}\approx \sqrt{3.41241}>X_1 \] Assume that \(X_n>X_{n-1}\), check \(X_{n+1}\) \[ \begin{align*} X_{n+1}&=\sqrt{2+X_n}\\ X_{n+1}^2&=2+X_n\\ X_n^2&=2+X_{n-1}\\ X_{n+1}^2-X_n^2&=2+X_n-2-X_{n-1}\\ &>2+X_n-2-X_n=0\quad\text{since }X_n>X_{n-1}\text{ by induction hypothesis}.\\ X_{n+1}^2&>X_n^2\\ X_{n+1}&>X_n \end{align*} \]
what is happening here: \[X ^{2}_{n+1}-X ^{2}_{n}=2+X _{n}-2-X _{n-1}\] and then the next row\[>2+X _{n}-2-X _{n}=0\] where does the \[X _{n-1}\] go? @thomas5267
Replaced\(X_{n-1}\) with \(X_n\) and changed = to > since we assumed that \(X_n>X_{n-1}\). The induction hypothesis is the assumption.
just curious @pate16 what do you not understand about this: \[x_{n+2}^2=2+x_{n+1}>2+x_n=x_{n+1}^2\] given \[x_{n+1}>x_n\]
like you do know that: \[x^2_{n+2}=2+x_{n+1} \text{ and that } x_{n+1}^2=2+x_n \text{ right ? }\]
\[\text{ if } x_{n+1}>x_n \\ \text{ then } 2+x_{n+1}>2+x_n\]
so this is what we have: \[X _{1}=\sqrt{2}\] \[X _{n+1}=\sqrt{2+Xn}\] and we want to show that \[X _{n+1}>X _{n}\] for alla integers n>1 1)(i.b) n=1 showed us that \[X _{2}>X _{1}\] 2)(steps) retriceuming that the assertion above is true for n=p \[X _{p+1}>X _{p}\] since \[X _{p+1}=\sqrt{2+X _{n}}\] it says \[\sqrt{2+X _{n}}>X _{p}\] we now want to show that the assertion applies to the nextcoming integer, i.e p+1 \[\sqrt{2+X _{p+1}}>Xp+1 \] substitution for x_p+1\[(\sqrt{2+\sqrt{2+X _{p}}})^{2}>(\sqrt{2+X _{p}})^2\] \[2+\sqrt{2+X _{p}}>2+X _{p}\] -2 both sides \[\sqrt{2+x _{p}}>x _{p}\] which shows that \[X _{n+1}>X _{n}\] cause its the same
Is this correct? @freckles
@IrishBoy123 you gotta help me out on this one! Im all stuck and it feels like the more I read the dumber I get
let me try paraphrase the advice @freckles gave do the plugging in bit of course at n = 1 or whatever , but at the heart of it is this idea assume \(x_{k+1} > x_k\) is true , ie for n = k we know from the definition that \(x_{k+2}^2 = 2 + x_{k+1}\) we also know that \(2 + x_{k+1} > 2 + x_{k}\) because we assumed \(x_{k+1} > x_k\) and we know that \(2 + x_{k} = x_{k+1}^2\) from the definition ***so we now know that assuming \(x_{k+1} > x_k\) is true , ie for n = k then \(x_{k+2}^2 >x_{k+1}^2 \) is also true
and if it's any consolation, these things give me a sore head too ;-)
@IrishBoy123, so thats it with no calculation whatsoever? Is that just true..?
you do know in induction: we show the base case then we assume for some integer k blah blah is true then we show it is true for k+1 ?
Yes
\[\text{ Base case } x_{2}=\sqrt{2+x_1}=\sqrt{2+\sqrt{2}}>\sqrt{2} \text{ since } 2+\sqrt{2}>2 \\\] \[\text{ Our assumption } x_{p+1}>x_p \text{ for some integer } p>1 \\ \text{( since you like to use the letter) } p\] \[\text{ What we want to show } x_{p+2}>x_{p+1}:\] \[\text{ Now remember our sequence is } x_{p+1}=\sqrt{2+x_p} \\ \text{ or squaring both sides } x^2_{p+1}=2+x_p \\ \text{ ok I'm going to replace } p \text{ with } p+1 \\ x^2_{p+1+1}=2+x_{p+1} \\ x^2_{p+2}=2+x_{p+1} \\ \text{ but remember in our assumption we got to assume } x_{p+1}>x_p \\ \text{ so we have } x^2_{p+2}=2+x_{p+1}>2+x_p \\ \text{ but remember that } x_{p+1}^2=2+x_p \text{ so we have } x^2_{p+2}=2+x_{p+1}>2+x_p=x^2_{p+1} \\ \text{ this says } x^2_{p+2}>x^2_{p+1} \\ \text{ which means } x_{p+2}>x_{p+1}\]
so it isn't just true we proved it is true by induction
so it is true I just didn't want you to think we weren't doing anything to prove it because we did
there's a really hacky way to do this because \(x_{n+1} = \sqrt{2 + x_{n}}\) we have \(2 = x_{n+1}^2 - x_n = x_{n+2}^2 - x_{n+1} \) \( x_{n+1} - x_n = x_{n+2}^2 - x_{n+1}^2 \) so if you assume the LHS is >0, so must the RHS etc
Haha, I got it now!!! thanks alot everyone @freckles, @IrishBoy123 and @thomas5267 damn, I was just overthinking it I believe...
are you supposed to be learning induction or would any proof do?
Im learning induction!!@IrishBoy123
well, i hope you enjoyed this induction into induction :-)
haha yes, I dont know what I was thinking at first..im gonna close this one now, thanks again guys!

Not the answer you are looking for?

Search for more explanations.

Ask your own question